Global Survey on Consumer Protection and Financial Literacy : Oversight Frameworks and Practices in 114 Economies - World Bank (Washington, DC, 2014)
Financial consumer protection and financial education policies, in conjunction with the regulation of financial institutions and markets, need to ensure safe access to financial services and support financial stability and financial inclusion objectives. Consumer protection and financial literacy can contribute to improved efficiency, transparency, competition, and access to retail financial markets by reducing information asymmetries and power imbalances among providers and users of financial services. Rapid progress toward widespread financial inclusion must be appropriately complemented with checks and balances that ensure a responsible provision of financial services and products. A number of international efforts are in place to improve dialogue and identify best practices in financial consumer protection. To contribute to the international dialogue on financial consumer protection the World Bank in conjunction with Fin-CoNet, an international cooperation platform for supervisory agencies in the area of financial consumer protection, conducted a global survey on consumer protection and financial literacy to collect information from financial regulatory agencies in 114 economies. This brief summarizes the key results of the survey and accompanies the release of the data collected to provide timely feedback on the results.